ASAP! GIVING BRAINLIEST! Please read the question THEN answer CORRECTLY! NO guessing. Show your work OR give an explaination.
![ASAP GIVING BRAINLIEST Please read the question THEN answer CORRECTLY NO guessing Show your work OR give an explaination class=](https://us-static.z-dn.net/files/d06/d1a0f73510c5d632c072efedfabcd435.png)
Answer:
B. 5x^2 -4
Step-by-step explanation:
(f+g)(x) = f(x) + g(x)
= (4x^2 +1) +(x^2 -5) . . . . . . substitute for f(x) and g(x)
= x^2(4 +1) +(1 -5) . . . . . . . . collect terms
(f+g)(x) = 5x^2 -4